The Effect of Corporate Social Responsibility on Company Value in Financial Sector Companies on the Indonesia Stock Exchange - Rijaluddin, Rijaluddin; Purwanto, Budi; E, Wita Juwita (Jurnal Manajemen, 2022)
Today’s company competition in Indonesia is getting tighter and more competitive. The company is an organization that has a specific purpose in running its business, every company wants to be able to meet the welfare and interests of its members and shareholders. This activity is known as Social Responsibility. Corporate social responsibility (CSR) emerged as an idea, companies are no longer faced with responsibilities that are based on a single bottom line, namely the value of the company which is reflected in its financial condition only. But the company’s responsibility must rest on the triple bottom line, where the bottom line apart from finance is also social and environmental, because financial conditions alone are not enough to guarantee the company’s value grows in a sustainable manner. The purpose of this study was to identify the effect of corporate social responsibility (CSR) disclosure on firm value with financial performance as a moderating variable. Data collection is carried out with data documentation based on financial reports and sustainability reports. All banking companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period are considered as the population of this study. The sample was selected using purposive sampling method. The number of research samples is 36 companies. This study uses Microsoft Excel and software Eviews12 with panel data regression model to test the hypothesis. At the 5% significance level, the results of the study show that CSR has a positive effect on the value of banking companies listed on the BEI, while financial performance is unable to moderate the effect of corporate CSR on firm value. In other words, CSR in banking has an effect on increasing the value of banking companies listed on the IDX.